Dependency-dependent interference: NPI interference, agreement attraction, and global pragmatic inferences - Xiang, Ming; Grove, Julian; Giannakidou, Anastasia (Frontiers in Psychology, 2013)
Previous psycholinguistics studies have shown that when forming a long distance dependency in online processing, the parser sometimes accepts a sentence even though the required grammatical constraints are only partially met. A mechanistic account of how such errors arise sheds light on both the underlying linguistic representations involved and the processing mechanisms that put such representations together. In the current study, we contrast the NPI (negative polarity items) interference effect, as shown by the acceptance of an ungrammatical sentence like “The bills that democratic senators have voted for will ever become law”, with the well-known phenomenon of agreement attraction (“The key to the cabinets are…”). On the surface, these two types of errors look alike and thereby can be explained as being driven by the same source: similarity based memory interference. However, we argue that the linguistic representations involved in NPI licensing are substantially different from those of subject-verb agreement, and therefore the interference effects in each domain potentially arise from distinct sources. In particular, we show that NPI interference at least partially arises from pragmatic inferences. In a self-paced reading study with an acceptability judgment task, we showed NPI interference was modulated by participants’ general pragmatic communicative skills, as quantified by the Autism-Spectrum Quotient (Baron-Cohen 2001), especially in offline tasks. Participants with more autistic traits were actually less prone to the NPI interference effect than those with fewer autistic traits. This result contrasted with agreement attraction conditions, which were not influenced by individual pragmatic skill differences. We also show that different NPI licensors have distinct interference profiles. We discuss two kinds of interference effects for NPI licensing: memory-retrieval based and pragmatically triggered.